Family social climate and resilience in students of 3rd, 4th and 5th year of secondary school - Moya Lozano, María Elena (2019)
The aim of this study was to determine the relationship between family social environment and resilience in third, fourth and fifth year students of the secondary level of an educational institution in the North of Peru.  This is a cross-sectional, descriptive and correlational design study, with a population of 394 students aged 13 to 19. The instruments used were the Moos family social environment scale and the Wagnild and Young resilience scale. The results show that there is a relationship between the family social environment and resilience (rs =. 175, p <. 05). Also, the dimension of family social climate called "interpersonal relationships" (rs =. 123, p <. 05) presents a significant relationship and "personal development" shows a highly significant relationship with "resilience" (rs =. 211, p <. 01). However, the "Stability" dimension does not have a correlation with resilience. Conclusions: From the analyzed data, it is concluded that social family climate is associated with resilience in adolescents.